Optical and Chemical Properties of Fragaria ananassa and Galena: Potential Photosensitizers in a Natural Dye-Sensitized Solar Cell - Akinsola, Ibukun S; Alabi, Aderemi B; Nicola, Coppede (Tanzania Journal of Science, 2021)
Dye is one of the major components for high power conversion efficiency in a dye-sensitized solar cell. There are challenges natural dyes encounter, especially with quick degradation of the dye molecules. This work considered mineral dye in comparison with plant dye to address the challenge of degradation of natural plant dyes. The optical properties and functional groups of the two natural dyes were studied in this work. The absorption spectra, the optical band gaps and the absorption coefficients of the dyes were reported and found to be suitable for use as photosensitizers in a dye-sensitized solar cell (DSSC), as they absorb in the visible region of the electromagnetic radiation. The functional groups were studied by carrying out Fourier transform infrared spectroscopy and the amine, carbonyl and hydroxyl groups present in both dyes confirmed promising material that can absorb solar radiation in the visible region (around 380–800 nm) and which finds application in fabricating DSSC. The organic compositions in the mineral dye are studied via the gas chromatography-mass spectrometry and the results justify the observation from the FTIR spectroscopy. The properties observed, via the characterizations techniques used, confirm materials suitable for use as photosensitizers in fabricating DSSC. Keywords: Plant dye, Mineral dye, Photosensitizer, Visible region, DSSC.